2007
DOI: 10.1002/nme.2180
|View full text |Cite
|
Sign up to set email alerts
|

Mass lumping strategies for X‐FEM explicit dynamics: Application to crack propagation

Abstract: SUMMARYThis paper deals with the numerical modelling of cracks in the dynamic case using the extended finite element method. More precisely, we are interested in explicit algorithms. We prove that by using a specific lumping technique, the critical time step is exactly the same as if no crack were present. This somewhat improves a previous result for which the critical time step was reduced by a factor of square root of 2 from the case with no crack. The new lumping technique is obtained by using a lumping str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 24 publications
1
116
0
Order By: Relevance
“…We focused our study on cracks, free boundaries and holes modelling with X-FEM. We showed that the proposed lumping formula is a generalization of some lumping techniques that were proposed for discontinuous enrichment for cracks (see [24,25]) and for free boundaries for constant strain elements (see [35]). …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We focused our study on cracks, free boundaries and holes modelling with X-FEM. We showed that the proposed lumping formula is a generalization of some lumping techniques that were proposed for discontinuous enrichment for cracks (see [24,25]) and for free boundaries for constant strain elements (see [35]). …”
Section: Discussionmentioning
confidence: 98%
“…The discrete problem can therefore be written as a classical finite element dynamic problem given in Eqs. (25) to (27).…”
Section: Numerical Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[18]. In comparison with implicit analyses, the number of timesteps for dynamic fracture is increased with an explicit time scheme, but the explicit inversion of the diagonal mass matrix makes the computational cost per time step much lower [16].…”
Section: Quasi-explicit Sovlermentioning
confidence: 99%
“…The time condition is half of that for a standard FEM solution to resolve the Heaviside function as XFEM crosses an element (discussed in the next section) [18].…”
Section: Quasi-explicit Sovlermentioning
confidence: 99%